2014
DOI: 10.5539/enrr.v4n3p23
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of farmers in Bangladesh to Asian Elephants (Elephas maximus) as an Agricultural Pest in

Abstract: We explored the degree to which Bangladeshi farmers perceive Asian elephants (Elephas maximus) as agricultural pests, as related to the type of farming and other demographic profile of the farmers. We analysed the size and cropping patterns of farms raided by wild elephants, the extent and nature of crop loss, the months and crop-raiding time; and the size of elephants' herds that caused crop-raiding incidents. The average loss of entire crops increased with distance from the park up to 300 m and then decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…In many parts of Africa, wildlife populations and the human communities living alongside them often compete over land and the natural resources therein. This often results in harmful interactions between them and can result in, among other, loss of crops or physical injuries ( Madden, 2004 ; Sarker, 2010 ). These unwanted interactions only intensify with increasing human populations, and have become a pressing matter for many countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of Africa, wildlife populations and the human communities living alongside them often compete over land and the natural resources therein. This often results in harmful interactions between them and can result in, among other, loss of crops or physical injuries ( Madden, 2004 ; Sarker, 2010 ). These unwanted interactions only intensify with increasing human populations, and have become a pressing matter for many countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Mean crop damage losses and the frequency with which crop damage by elephants was reported were greatest < 1 km from the Rungwa, Kizigo and Muhesi Game Reserves. Other studies have also shown that farms close to protected areas experience more crop damage compared to those further away (Nahonyo, 2005; Okello et al, 2008; Sarker, 2010; Blair & Meredith, 2017). However, estimates of crop losses caused by elephants can be exaggerated by affected communities (Enukwa, 2017; Shaffer et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…In human-modified landscapes, animals with large home ranges, such as the African and Asian Elephas maximus elephants, may enter fields, causing crop damage either by foraging on crops or trampling (Gubbi, 2012; Blair & Meredith, 2017; Shaffer et al, 2019). Human–elephant interaction is a major challenge facing the management of protected areas in both Africa and Asia (Sarker, 2010; Gubbi, 2012; Mace et al, 2018). The negative impacts of elephants are associated with increasing settlement and farming activities close to protected areas.…”
Section: Introductionmentioning
confidence: 99%
“…During 2000–2018, 78 people died and 68 were injured by elephants in the study area, with c. 42% of fatalities reported in crop fields (as a result of crop-guarding) and c. 38% in homes (Aziz et al, 2016). Household destruction and agricultural losses were the most common types of damage reported, with villages closer to forests suffering more (Sarker & Røskaft, 2014). Conflict is linked to degradation of the elephants’ habitat as a result of unregulated firewood collection (residents have no other energy source for cooking), overgrazing and the clearing of remaining secondary forest for acacia plantations (Islam et al 2011).…”
Section: Study Areamentioning
confidence: 99%